Implikasi Pengelolaan Kelas Bilingual Terhadap Peningkatan Mutu Siswa Sekolah Menengah Pertama MTs. Hidayatul Muttallimin Sidoarjo - Fathul Fauzi (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2020)
This study was conducted to examine the implications of bilingual classroom management on improving the quality of students in MTs Hidayatul Muttallimin Sidoarjo with the aim to find out how the management of bilingual classes in MTs Hidayatul Muttallimin Sidoarjo, how to improve the quality of students in MTs Hidayatul Muttallimin Sidoarjo, and how the implications of bilingual class management on improving the quality of students at MTs Hidayatul Muttallimin Sidoarjo. This type of research uses quantitative research. And data collection is done by questionnaire, observation, interview and documentation. Then the data is analyzed using a statistical formula, namely: the formula of the formula and the formula of product moment and coupled with the regression formula. The results of this study, show that the management of the bilingual class MTs Hidayatul Muttallimin Sidoarjo in the implementation process can run effectively and efficiently or is classified as good, because the percentage calculation results show between 56% -100%. And improving the quality of students in MTs Hidayatul Muttallimin Sidoarjo after entering the bilingual class has increased in the achievement of sufficient performance results, this is based on the calculation of the percentage of questions peritem the value obtained is between 56% -75% with criteria classified as sufficient. While in its implications the management of bilingual classes in MTs Hidayatul Muttallimin Sidoarjo has positive implications (impacts / effects) on improving the quality of students in high or strong categories. This, based on the product moment calculation results, the results obtained are 0.71 and the barada interpretation table at the value of r = 0.70 - 0.90 indicates that between variables X and Y there are strong or high implications. Likewise with the results of the calculation of the regression formula shows that the management of bilingual classes has a positive relationship with improving the quality of students with a value of 0.711.